Characteristics of Liquid Smoke From Young Coconut Shells at Various Pyrolysis Temperature - Ressa Fitra Adinda; Muhammad Faisal; Fauzi Muhammad Djuned (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: Young coconut shells contain wood components, such as hemicellulose, cellulose, and lignin. These compounds can be used as raw materials for liquid smoke. The physical and biological characteristics of liquid smoke from young coconut shells pyrolysed at various temperatures were investigated in this study. Specifically, young coconut shells were pyrolysed at 300°C–420°C in a slow pyrolysis reactor. To eliminate tar, the liquid smoke was distilled at 190°C. Further, the chemical content of the liquid smoke was quantified using Gas Chromatography-Mass Spectrometry (GC-MS). Acetic acid and phenol compounds were identified using high performance liquid chromatography (HPLC) and ultraviolet-vis spectrophotometry. The gas chromatography-mass spectrometry (GC-MS) data revealed that liquid smoke contains over 15 chemical components, including phenolic acid, carboxylic acid and its derivatives. Antibacterial, minimum inhibitory concentration (MIC) and minimum killing concentration (MKC) tests were performed to analyse the antimicrobial properties of liquid smoke in inhibiting the growth of Escherichia coli and Salmonella enterica sv Typhimurium. The pyrolysis temperatures affected the composition of the produced liquid smoke. The highest phenol and acetic acid content were found at 340°C and 380°C, where lignin is degraded into phenolic compounds and cellulose is degraded to produce acetic acid. The results of the antibacterial test showed that the maximum inhibition zone was obtained at 420°C, and at 340°C and 380°C the bacteria were inhibited and died.Abstrak: Tempurung kelapa muda mengandung komponen kayu seperti hemiselulosa, selulosa, dan lignin. Senyawa ini dapat digunakan sebagai bahan baku asap cair. Karakteristik fisik dan biologis asap cair dari tempurung kelapa muda yang dipirolisis pada berbagai suhu diselidiki dalam penelitian ini. Tempurung kelapa muda dipirolisis pada suhu 300 °C - 420 °C dalam reaktor pirolisis lambat. Untuk menghilangkan tar asap cair didistilasi pada suhu 190 °C. Selanjutnya, kandungan senyawa kimia asap cair dikuantifikasi menggunakan gas chromatography-mass spectrometry (GC-MS). Senyawa asam asetat dan fenol diidentifikasi menggunakan high performance liquid chromatography (HPLC) dan Spektrofotometri UV-Vis. Data gas chromatography-mass spectrometry (GC-MS) menunjukkan bahwa asap cair mengandung lebih dari 15 komponen kimia, termasuk asam fenolik, asam karboksilat dan turunannya. Uji antibakteri, Minimum Inhibitory Concentrantion (MIC) dan Minimum Killing Concentrantion (MKC) dilakukan untuk menganalisis sifat antimikroba asap cair dalam menghambat pertumbuhan Escherichia coli dan Salmonella enterica sv Typhimurium. Temperatur pirolisis mempengaruhi komposisi asap cair yang dihasilkan. Kandungan fenol dan asam asetat tertinggi ditemukan pada suhu 340°C dan 380°C, dimana pada suhu tersebut lignin terdegradasi menjadi senyawa fenol dan selulosa terdegradasi menghasilkan asam asetat. Hasil uji antibakteri menunjukkan bahwa zona hambat maksimum diperoleh pada suhu 420 °C, pada suhu 340 °C dan 380 °C bakteri ditemukan terhambat dan mati.